2003
DOI: 10.1029/2002jb001935
|View full text |Cite
|
Sign up to set email alerts
|

Response of subglacial sediments to basal freeze‐on 1. Theory and comparison to observations from beneath the West Antarctic Ice Sheet

Abstract: [1] We have constructed a high-resolution numerical model of heat, water, and solute flows in sub-ice stream till subjected to basal freeze-on. The model builds on quantitative treatments of frost heave in permafrost soils. The full version of the Clapeyron equation is used. Hence, ice-water phase transition depends on water pressure, osmotic pressure, and surface tension. The two latter effects can lead to supercooling of the ice base. This supercooling, in turn, induces hydraulic gradients that drive upward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 109 publications
6
125
0
Order By: Relevance
“…Any sediment present at SLW likely records some of that variability. Christoffersen and Tulaczyk (2003) indicated that the presently occurring freezing at the base in lower WIS tends to induce erosion of the subglacial sediments, evidenced by packages of accreted sediment in boreholes drilled into KIS (Engelhardt, 2004). The only areas not directly exposed to sediment erosion in this environment are the beds of subglacial lakes.…”
Section: Implications For Potential Findings At the Wissard Drill Sitementioning
confidence: 99%
“…Any sediment present at SLW likely records some of that variability. Christoffersen and Tulaczyk (2003) indicated that the presently occurring freezing at the base in lower WIS tends to induce erosion of the subglacial sediments, evidenced by packages of accreted sediment in boreholes drilled into KIS (Engelhardt, 2004). The only areas not directly exposed to sediment erosion in this environment are the beds of subglacial lakes.…”
Section: Implications For Potential Findings At the Wissard Drill Sitementioning
confidence: 99%
“…Newman and Wilson (1997) proposed a theoretical formulation for unsaturated soils using soil-freezing and soil-water characteristic curve data to combine the heat and mass transfer relationships into a single equation for freezing or frozen regions of the soil. Christoffersen and Tulaczyk (2003) constructed a high-resolution numerical model of heat, water, and solute flows in sub-ice stream till subjected to basal freeze-on. They proposed a formulation of the equilibrium relation without assuming zero ice pressure through the full version of the generalized Clapeyron equation (Mikkola and Hartikainen, 2001), which enables them to model segregation ice onto the freezing interface and so develop stratified basal ice layers.…”
Section: Freezing-soil Modelsmentioning
confidence: 99%
“…Kamb Ice Stream (formerly known as Ice Stream C) ceased fast flow about 150 yr ago (Retzlaff and Bentley, 1993) and the main trunk is now stagnant. This ice stream is thought to have thinned to the point where basal melting changed to basal freezing which removed water from the basal till causing stiffening of the substrate, a decrease in lubrication and eventual stoppage (Tulaczyk et al, 2000a, b;Bougamont et al, 2003;Christoffersen and Tulaczyk, 2003;Hulbe and Fahnestock, 2004;Catania et al, 2006).…”
Section: Introductionmentioning
confidence: 99%